Grazing Behavior and milk yield of Senegalese Sahel goat - Cisse, M.; Ly, I.; Nianogo, A.J.; Sane, I.; Sawadogo, J.G.; N'Diaye, M.; Awad, C.; Fall, Y. (Elsevier, 2002)
In northern Senegal, 49 Sahel does, 2.7± 0.5-year-old were observed over 1 year while foraging in natural pasture. Does were assigned to three treatments 2 weeks after kidding: ad libitum grazing (group 1), grazing plus daily supplementation with 500 9 per animal of concentrate, 66% corn flour, 30% groundnut cake, and 4% mineral and vitamin premix (group 2), and grazing plus 300g per animal of cottonseed (group 3). The grazing behavior of goats was assessed by direct bservation and the milk production was recorded weekly by the double weighing method (four times per day). Goats spent about 80% of their time eating, and time spent walking was higher in the dry season than in the rainy season (5-15% versus 0.6-2.6%). Contribution of ligneous species in the diet peaked in July (96.1 %) and January (95%), then decreased reaching 5% in September, corresponding to the peak intake of herbaceous species. The goats preferred the Acacia albida, Maytenus senegalensis and Piliostigma reticulata browse species, and the Ipomea pestigridis, Pennisetum pedicellatum and Brachiaria lata herbaceous species. Supplementation did not significantly affect milk yield, which peaked at week 3 (1158± 425g per day per animal) for does from group 1, at week 4 (1045 ± 343g per day per animal) for group 2, and at week 2 post-partum (980± 232 9 per day per animal) for those of group 3. In the first month of lactation, body weight (BW) of twins were 1.6 kg lower than singles (P < 0.05). From week 1 to 14 of lactation, does from group 1 lost more BW than those of group 2 (-0.7 kg versus -0.2 kg; P > 0.05). Plasma urea level was higher in the early stage of lactation then decreased from week 8 post-kidding. Glycemia peaked at 24-48 h post-partum.